Q-switched and mode-locked hafnium bismuth erbium -doped Fiber Lasers with New Passive Saturable Absorbers / Umi Namirah Zakaria - Umi Namirah , Zakaria (2022)
Topology Insulators (TIs) based nanomaterials have recently emerged as a promising solution for generating Q-switched and mode-locked fiber lasers. These lasers have high market potential for laser sensing and spectroscopy, material processing, and medical applications since since they are more compact in geometry and simpler in setup. Sharing some advantages from fiber technology, the developed laser is more robust, zero-alignment, and less operational cost. On the other hand, tremendous interests have also been focused on developing an efficient Erbium-doped fiber (EDF) with high Erbium ion concentration. This study aims to demonstrate fiber lasers operating at 1550 nm region using a newly developed Hafnium Bismuth Erbium co-doped fiber (HBEDF) as a gain medium. Q-switched and mode-locked HBEDF lasers (HBEDFLs) were demonstrated using a new passive saturable absorber based on topology insulator materials and a solid Bismuth-doped fiber (BDF). The HBEDF has high doping levels of Erbium ion (12500 wt ppm) through incorporation of Hafnium and Aluminum ions, which prevents the clustering effect. At the input signal power of –10 dBm, a flat gain of 10.9 dB was obtained operating within the wavelength region from 1525 to 1565 nm using only 0.5 m long of the active fiber. In this work, three types of TI based SA films were successfully developed; Bismuth (III) Telluride (Bi2Te3), Bismuth (III) Selenide (Bi2Se3) and Antimony Telluride (Sb2Te3). Q-switched fiber lasers were then demonstrated using a highly doped HBEDF as a gain medium and bismuth ions-based materials (topological insulator and BDF) as a passive SA. For instance, by employing a Bi2Se3 PVA film as SA in HBEDFL cavity, the self-started Q-switched pulse trains operating at 1562 nm was obtained. The pulses have a shortest pulse duration of 4.4 μs and maximum pulse energy of 41.1 nJ. The pulse frequencies were tunable from 53.4 to 73.0 kHz with a pump power variation from 96 to 166 mW. Passively Q-switched and mode-locked HBEDFLs were also successfully demonstrated using two types of antimony based SAs; Sb2Te3 and pure Sb PVA films. By incorporating the Sb2Te3 PVA film in HBEDFL cavity, a nanosecond mode-locked laser was obtained with 1 MHz repetition and 350 ns pulse width. The mode-locking pulses achieved the maximum pulse energy of 2.04 nJ at 240.8 mW pump power. In another work, a passively mode-locked HBEDFL was demonstrated using the pure Sb film as a SA. Stable mode-locked pulses were successfully obtained within a pump power range from 198 mW to 300 mW. The laser was capable to generate optical soliton pulses centered at 1559.7 nm with the full width at half maximum of 0.52 nm and repetition rate of 1.0 MHz. The pulse duration and energy were 4.96 ps and 4.85 nJ, respectively. These findings show that HBEDF has a great potential for short and ultra-short pulses generating while TIs and antimony materials have also a great potential in photonic applications.